Monitoring Outcome of Joint Arthroplasty in Italy: Implementation of the National Registry - Torre, Marina; Romanini, Emilio; Zanoli, Gustavo; Carrani, Eugenio; Luzi, Ilaria; Leone, Luisa; Bellino, Stefania (Joints, 2017)
Purpose Arthroplasty registries have an important role in improving outcomes in joint surgery. As the demand for joint arthroplasty continues to increase, growing attention is being paid to the establishment of national registries, which contribute to the enhancement of the quality of patients' care. Indeed, providing postmarketing surveillance data in terms of safety and effectiveness of medical devices, registries contribute to the best orthopaedic practice and support public health decision making. In this context, a project aimed at implementing a national arthroplasty registry in Italy has appeared to be essential, and the activities performed in the last years have consolidated data collection of hip and knee replacements.Methods Based on a close cooperation among public health institutions, clinicians, and involved stakeholders, the architecture of the registry is built on three pillars: (1) data collected using Hospital Discharge Records (HDRs) integrated by an additional dataset, (2) implants identified and characterized in a dedicated medical devices library, and (3) a federation of regional registries coordinated by a public health institution, the Italian National Institute of Health.Results Besides the organizational structure, statistical analyses on joint arthroplasty from national HDR database (2001–2014) and Italian registry data (2014) are presented. Currently, the institutions participating in the registry on a voluntary basis show 80% of completeness for hip and 58% for knee, and represent approximately 18% of the national volume.Conclusion To make data collection effective, participation should be mandatory and ruled by a national law.Level of Study Level III, observational analytic study.
Keywords: arthroplasty registry; hip arthroplasty; knee arthroplasty; medical device